Demokrasi Perspektif Hizbut Tahrir versus Religious Mardomsalari ala Muslim Iran - al-Amin, Ainur Rofiq (Program Pascasarjana UIN Sunan Ampel Surabaya, 2013)
In general, Muslim responses to democracy are threefold. The first is the Muslim group which accepts without reserve the concept of democracy. This group appreciates the discourse of democracy as such without any criticism. The second is the Muslim group which accepts democracy with criticism. This group tries to elaborate democracy which is in line with culture, tradition and religion in a particular country. This group rejects to be dictated by the Western model of democracy. The third is the Muslim group which rejects democracy. This group regards democracy as the source of evil and crimes. One that belongs to the third group is Hizbut-Tahrir Indonesia (HTI). According to HTI, democracy is evil, incompatible with Islam. For this reason, this articles focuses on, first, the factors which lead HTI to reject democracy; second, the reason or Islamic legal construct developed by HTI to reject democracy; and third, religious mardomsalari (religious democracy) practiced in the Islamic Republic of Iran. This study is a qualitative research based on the study of texts.